Comparative evaluation of tar steam reforming over graphitic carbon supported Ni and Co catalysts at low temperature. (15th September 2021) - Tang, Wen; Cao, Jing-Pei; Wang, Zhi-Hao; He, Zi-Meng; Liu, Tian-Long; Wang, Ze-Ying; Yang, Fei-Long; Ren, Jie; Zhao, Xiao-Yan; Feng, Xiao-Bo; Bai, Hong-Cun
Graphical abstract: Highlights: Metallic Co highly dispersed on char using lignite as carbon precursor. The Co nanoparticles loaded by ion exchange method are smaller than Ni. The interaction between Co and lignite is stronger than Ni. Co/modified lignite char efficiently catalyzes tar cracking at low temperature. The oxygen affinity of Co is key to carbon-deposition resistant. Abstract: The development of cheap and highly dispersed nano-catalyst is one of the key technologies for low temperature steam reforming (SR) of biomass tar. This work used acid-washed and oxidized Shengli lignite char (OXAWSL) as carbon precursor to load Co (Co/OXAWSL) and Ni (Ni/OXAWSL) via ion exchange method to SR of toluene and biomass tar. The Co/OXAWSL was more active and stable than Ni/OXAWSL during the 30 h test with a final toluene conversion of 85% at a relatively low temperature of 450 °C and steam to carbon ratio (S/C) of 3.4, which resulted from its small particle size (5.6 nm) and high dispersion (12.3%) of Co. The relatively high H2 production (42.59 mmol/g-biomass) over Co0.1 /OXAWSL (450 °C, S/C = 3.4) in SR of tar was also obtained. A low E a (22.0 kJ/mol) value of Co/OXAWSL and good affinity to oxygen for Co explained its excellent performance. The low-temperature tar cracking process can provide theoretical and technical support for the large-scale industrial utilization of biomass pyrolysis and gasification.